The Efficacy of Impact-Absorbing Materials during Collision with a Soccer Ball - Zahari, Taha; Mohd Hasnun Ariff, Hassan; Mohd Azri, Aris (Scientific.Net, 2013)
The uniqueness of soccer is that the players are allowed to use their head to pass the ball to a teammate of even try to score goal. Studies have shown that heading in soccer might be dangerous to the brain and could lead to brain trauma. There are headgears available for soccer players to protect their head, but studies have proven that currently available headgears are ineffective in reducing the impact caused by a soccer ball. The objective of this study is to test the efficacy of six different types of impact-absorbing materials in reducing the linear impact force from a soccer ball. The soccer ball was dropped from the height of 2.3 m onto a force platform to measure the impact force. A high-speed camera is used to record the motion and the impact duration, and then the coefficient of restitution for each impact was determined. Polyurethane (PU) comb-gel was found to be the most effective material in reducing the peak impact force and impulse compared with other materials. The reduction in peak force was associated with longer impact duration between the soccer ball and the PU comb-gel. However, the coefficient of restitution was reduced by 21.7%, implying that using the gel alone will reduce the speed of the ball after heading, thus reducing the performance of a player wearing it. A combination of PU gel and another stiffer material is suggested and the effectiveness of the composite will be the subject of future investigation.